2002
DOI: 10.1016/s0893-133x(02)00361-5
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Mood Response to Acute Tryptophan Depletion A Reanalysis

Abstract: Acute tryptophan depletion (ATD) induces depressive symptoms in 50-Acute tryptophan depletion (ATD) is a technique used to study serotonin (5-hydroxytryptamine; 5-HT) brain function in mood disorders. In this paradigm, 5-HT function is temporarily lowered by deprivation of its precursor L -Tryptophan (Trp), an amino acid essential for 5-HT synthesis. It has been suggested that behavioral response to ATD might be informative about the pathophysiology of clinical depression and the mechanisms mediating antidepre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
136
3
4

Year Published

2003
2003
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(158 citation statements)
references
References 42 publications
(37 reference statements)
15
136
3
4
Order By: Relevance
“…Although the present study found no significant relationship between recurrent depression and response to ATD, recurrent depression was the most powerful predictor of ATD response in a previous study (Booij et al, 2002). Other ATD studies also support this association (Neumeister et al, 2004;Smith et al, 1997).…”
Section: Discussioncontrasting
confidence: 62%
“…Although the present study found no significant relationship between recurrent depression and response to ATD, recurrent depression was the most powerful predictor of ATD response in a previous study (Booij et al, 2002). Other ATD studies also support this association (Neumeister et al, 2004;Smith et al, 1997).…”
Section: Discussioncontrasting
confidence: 62%
“…Against this we have demonstrated that the related procedure of TRP depletion, administered in an identical placebocontrolled crossover design, causes significant depressive relapse in a similar group of recovered depressed subjects (Smith et al, 1997). Indeed a recent review of the effects of TRP depletion in recovered depressed patients suggested that female subjects with a history of multiple episodes were particularly at risk of clinical depressive relapse (Booij et al, 2002).…”
Section: Discussionmentioning
confidence: 79%
“…The women in the present study had mostly been recovered for long periods of time and it is possible that long duration of remission may make subjects less vulnerable to the mood lowering effects of monoamine depletion. However, the literature on TRP depletion does not support this possibility (Booij et al, 2002). All our subjects had at some time point met criteria for the melancholic subtype of depression because we predicted that subjects who had experienced anhedonia might be more vulnerable to lowered DA function.…”
Section: Discussionmentioning
confidence: 95%
“…This reduction is achieved by selectively excluding the essential amino acid tryptophan, the precursor to 5-HT, from the diet (Young et al, 1985). The most well-known effect of ATD is to produce a temporary recurrence of some depressive symptoms in a proportion of patients who have previously experienced a major depressive episode but who are euthymic at the time of testing (Booij et al, 2002). This effect appears to be most marked in patients maintained on selective serotonin reuptake inhibitors (SSRIs), though mood change in unmedicated remitted major depressive disorder patients has also been reported (Neumeister et al, 2004).…”
Section: Introductionmentioning
confidence: 99%